Design Optimization of a Novel Receiving Cavity for Concentrated Solar Power Applications by Means of 3D CFD Simulations. (May 2015) - Gaetano, A.; Zavattoni, S.A.; Barbato, M.C.; Good, P.; Ambrosetti, G.; Pedretti, A.
Abstract: The aim of this work was the design optimization, by means of accurate steady state 3D CFD simulations, of a novel receiving cavity for Concentrated Solar Power (CSP) applications. The receiving cavity has been developed by Airlight Energy Manufacturing SA in collaboration with ETH Zurich and SUPSI-DTI-ICIMSIwithin the framework of the SolAir-2 project. It is made of a helically coiled steel tube, and resulted highly effective in converting the radiative energy coming from the sun into thermal energy gathered by air which was selected as heat transfer fluid (HTF) being cheap, environmentally friendly and suitable for high temperatures applications. The main geometrical parameters considered for the optimization were: cavity height, varied by increasing or decreasing the number of coils, cavity external diameter, and the presence of a spiral coiled tube closing the cavity top. For each configuration the air flow rate, with an inlet temperature of 120 °C, was tuned in order to reach an outlet temperature close to the target value of 650 °C. Cavity performance were evaluated in terms of thermal efficiency and pressure drop under two different skew angle conditions for the incoming solar radiation, 18° and 40°. CFD simulations were performed with Ansys Fluent. Navier-Stokes and energy equations were numerically solved using the finite-volume method approach; radiation heat transfer inside the cavity was taken into account by means of the Discrete Ordinates (DO) radiation model.